2019
DOI: 10.1021/acs.jafc.8b05915
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of the Skin-Specific Accumulation of Anthocyanins in Black Peanut (Arachis hypogaea L.)

Abstract: As an oil crop with good taste and profuse nutrition, peanut (Arachis hypogaea L.) is grown worldwide, mainly for edible seeds. Black peanuts attract more attention for their appealing color and health-promoting anthocyanins. Here, two cyanidin-based anthocyanins and four quercetin-based flavonols were separated and identified from skins of two black cultivars (Zi Yu and Zi Guan) by HPLC-ESI-Q-TOF-MS. To study the anthocyanin accumulation, libraries constructed from the mRNA of skins of Zi Yu and white cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…Anthocyanins are the main water-soluble pigments widespread in many flowering plants. The red, blue, and purple colors found in various plant tissues, including flowers, leaves, fruits, and seeds, are mostly attributed to the accumulation of anthocyanins 13 . In addition to their well-known physiological functions of serving as pollinator and seed disperser attractants, anthocyanins also play essential roles in protecting plant tissues from being damaged by high light, UV radiation, cold, drought, nutrient deficiency, and pathogen attack 4 ; anthocyanins also act as important health-promoting supplements in the human daily diet.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are the main water-soluble pigments widespread in many flowering plants. The red, blue, and purple colors found in various plant tissues, including flowers, leaves, fruits, and seeds, are mostly attributed to the accumulation of anthocyanins 13 . In addition to their well-known physiological functions of serving as pollinator and seed disperser attractants, anthocyanins also play essential roles in protecting plant tissues from being damaged by high light, UV radiation, cold, drought, nutrient deficiency, and pathogen attack 4 ; anthocyanins also act as important health-promoting supplements in the human daily diet.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA samples of drought-stressed leaf were used for qRT-PCR analysis following the method described in previous studies [24]. Gene-specific qRT-PCR primers were designed using the Primer 5 software and listed in Additional file 1: Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…This shows that more delphinium is produced in the black fruit than cyanidin. Previous studies have shown that LrDFR and LrFLS share the same upstream substrates (e.g., DHM, DHQ, and DHK) and take a large proportion of total flavonoids in plants (Huang et al, 2019). In black fruits, the rate-limiting enzyme LrDFR specifically binds DHQ to synthesize delphinidin and its derivatives and has little binding to other substrates.…”
Section: Degs Involved In Flavonoid Metabolism Between Two Fruit Varimentioning
confidence: 99%